Pengembangan Layout Desa Wisata Camping Ground Desa Wonorejo Kecamatan Singosari - Al Qadri R, Muh. Aimar; Ilham, Muhammad; Kusdodo, Hendri; Musthofa A, M. (Universitas Ngeri Malang, 2023)
Wonorejo is a village that has great potential in the tourism sector. Its location not far from the economic center in Singosari village makes it easily accessible. One of the potentials that can be developed is the camping ground where there is a hill with an exciting view to become a camping tourist destination. The view of Malang Raya, wrapped by beautiful mountain kawi, can be seen from the hill. The existence of this camping ground can also improve the village's economy. This is because the village will be more often visited by tourists who feel the sensation of the Wonorejo campground. The surrounding community can undoubtedly take this momentum to market the original work of the village or can also be a provider for tourists. Wonorejo merupakan desa yang memiliki potensi besar pada sektor pariwisata. Letaknya yang berada tidak jauh dari pusat perekonomian di kelurahan singosari membuatnya mudah diakses. Salah satu potensi yang dapat dikembangkan yaitu camping ground yang mana terdapat sebuah bukit memiliki view yang menarik untuk menjadi destinasi wisata perkemahan. Dari bukit tersebut dapat terlihat pemandangan Malang Raya yang dibalut oleh gunung kawi yang indah. Adanya camping ground ini pun dapat meningkatkan perekonomian desa. Hal ini karena desa akan lebih sering dikunjungi oleh wisatawan yang ini merasakan sensasi pada bumi perkemahan wonorejo. Masyarakat sekitar tentunya dapat mengambil momentum ini untuk memasarkan karya orisinil desa atau pun dapat menjadi penyedia bagi para wisatawan.